Sizing and applications of battery energy storage technologies in smart grid system: A review - Sufyan, Muhammad; Rahim, Nasrudin Abd; Aman, Muhammad Mohsin; Tan, Chia Kwang; Raihan, Siti Rohani Sheikh (AIP Publishing, 2019)
Dynamics of the world are changing, and people are preferring low cost and reliable power throughout the day. The addition of renewable energy to the existing system is also one of the ways to provide reliable and cheap electricity. The existing bottle neck in transmission lines, continuous contamination of the environment due to heavy reliance on fossil fuels, and the highly fluctuating cost of fossil fuel are few reasons for the widespread use of renewable energy technology. Energy storage technologies are the need of time and range from low capacity mobile storage batteries to high capacity batteries connected to the intermittent renewable energy sources. Selection of different battery types, each having distinguished characteristics in power and energy, depends on the nature of power required and delivered. This paper presents a detailed review of battery energy storage technologies pertaining to the latest technologies, benefits, sizing considerations, efficiency, cost, and recycling. An in-depth analysis in terms of advantages and limitations between the different types of batteries is discussed and compared. In terms of microgrid application, the economic benefits of battery sizing using optimization and probabilistic methods provide a potential solution during the design stage by taking into account various factors affecting the sizing of the battery such as the degradation rate, reliability, and battery placement. This paper ends with the discussion on the recyclability of these batteries and their impact on the environment. © 2019 Author(s).